Regularities in semantic change: a case study in the domain of junctions - Longhin, Sanderleia Roberta [UNESP] (Univ Fed Rio De Janeiro, Fac Letras, 2016)
The aim of this paper is to analyze regular patterns in semantic change based on the description, from a longitudinal perspective, of two courses of semantic-pragmatic change followed by the junction enquanto, which have originated expressions of meaning with a higher level of subjectivity: contrast, which arises from a perception of difference, incompatibility or conflict between entities comparable at some level; and condition, which results from the creation of hypothetical scenarios, based on reality or not. Following a theoretical model which assigns a key role to pragmatics in semantic change (TRAUGOTT; DASHER, 2002) and considering the corpus to be composed of texts in different genres ranging from the 18th to the 21st century, I focus primarily on the weight of source meanings, the kind of context leading to the emergence of polysemy and the status of the new meanings.
Keywords: semantic change; junction; polysemy; context